Mononuclear phagocytic system and fibrosis: back to the future?. Issue 3 (11th March 2021) - Ask, Kjetil; Vierhout, Megan; Dvorkin-Gheva, Anna; Shi, Wei
Bronchiolitis obliterans syndrome (BOS) is a chronic lung allograft dysfunction following lung transplantation [1–3], with histopathological characteristics of obliterative bronchiolitis (OB) that includes small airway epithelial disruption, submucosal inflammation and fibrosis, and obstruction of airway lumen. Clinical diagnosis is based on persistent decline of the allograft lung function measured by forced expiratory volume in 1 s and/or forced expiratory flow at 25–75% of forced vital capacity. 50% or more of lung transplantation recipients who survive beyond 5 years develop BOS, accounting for significant cases of lung transplantation failure and the leading cause of death for recipients who survived beyond 1 year after transplantation [4]. The mononuclear phagocytic system is a key player in fibrotic disease https://bit.ly/3nVIlbQ